COVID-19: A SYSTEMATIC REVIEW OF IMPLICATIONS FOR TRADE COMPETITIVENESS - Sharul Shahida Shakrein Safian; Norashida Othman; Nur Azirah Zahida Mohamad Azhar; Siti Norida Wahab (International Journal of Accounting, Finance and Business, 2021)
Trade is essential to keep supply chains flowing, especially for essentials products during the unprecedented global spread of the novel coronavirus diseas e 2019 (also known as the COVID-19 pandemic). Since the beginning of the pandemic, scholars have been studying and publishing research on various trade competitiveness issues. However, although the number of papers on this topic has gradually increased, it remains uncertain on what aspects of this disruption have already been examined and what aspects still need to be explored because of the absence of any systematic reviews of literature. The method of systematic literature review (SLR) is adapted to systematically review the existing research on the COVID-19 pandemic in trade disciplines. To carry out this systematic review, the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method has been utilized to attain an organized and adequate structure of the manuscript. Two leading bibliography databases namely Scopus and Web of Science have been searched using â€œCOVID-19â€ and â€œTrade Competitivenessâ€ as keywords. Through a rigorous and systematic search, this study reveals the methodologies, background, and ideas used in each research alongside the synthesis of the results. This study offers research directions for further analysis by combining the findings of these studies. These guidelines will help researchers in the design and conducted impactful research focusing on export competitiveness.